UJI VALIDITAS DAN REALIBILITAS SKALA TUGAS PERKEMBANGAN SISWA KELAS X SMA NEGERI 2 SIAK HULU - Azhari '; Tri Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The aims of this study are; 1) to know the level of duty validity scale development on students of SMA Negeri 2 Siak Hulu in Academic Year 2012/2013. 2) To know the level of duty reliability scale development on students of SMA Negeri 2 Siak Hulu in academic Year 2012/2013. The population in this study was also used as saturated sample, it meant that all members of populationas well as a member of as many as 204 samples. The method of study was a descriptive analytic method. The data collection tool was using the adjustment level developed by the writer. Technique analysis data was using to search for the validity of the formula used by the Product Moment Pearson SPSS 18 for windows with correlate bivariate, while the techniques used for reliability Cronbachal phausing SPSS 18 for windows. based on results of data analysis, the writer concluded that 1) Of the 60 items level adjustment there were 38 items that could besaid to be valid and invalid item 22, item-item valid ranged from -0,158 until 0,404. 2) The scale of the task of reliability developments with the formula Cronbachal phausing SPSS 18 for windows was obtained 0.672 reliable level.Key Words : validity, reliability, The development of duty